ANALYSIS OF READING INTEREST OF GRADE X-11 STUDENTS IN READING LITERATURE - Fatwa, Gisela Sagita Nur; Farrar, Abigail; Wulandari, Citra Eka (International Journal of Language and Culture, 2025)
Reading is one of the important things in all kinds of learning processes. Through reading, various knowledge, which can lead to success, can be obtained. The purpose of this study was to determine the interest of class X-11 students in reading literature, both Sundanese literature and Indonesian literature. The results of the study showed that class X-11 students of SMAN 7 Tasikmalaya prefer to read stories in Indonesian compared to Sundanese. Some students said that Sundanese has many words that are very difficult to. understand, making them have to read repeatedly to understand. The method used in this study was descriptive qualitative, with a questionnaire distribution technique to class X-11 students of SMAN 7 Tasikmalaya. Based on the results of the analysis, it can be concluded that the reading interest of class X-11 students of SMAN 7 Tasikmalaya is still at a varying level, with a tendency to be quite low. Factors that influence include the availability of interesting reading materials, the use of more dominant digital media, and the lack of literacy culture in the school and family environment. Therefore, collaborative efforts are needed from schools, teachers, and parents to increase students’ motivation and interest in reading by providing adequate reading facilities, interesting literacy programs, and consistent support.